High yield synthesis of boron-based nanosheets. (19th May 2019) - Saraswat, Rohit; James, Asha Liza; Jasuja, Kabeer
ABSTRACT: We present the chemical exfoliation of magnesium diboride (MgB2 ) by employing organic chelating agents for synthesising boron-based nanosheets in high yield. MgB2 is a promising parent material towards realising quasi-2D forms of boron, owing to its unique layered constitution: graphenic boron planes interleaved with hexagonal arrays of Mg atoms. Chelating agents can selectively extract the interlayer Mg from MgB2 in water, to form Mg-chelant complexes. The loss of Mg results in delamination of MgB2 into boron-based nanosheets. This approach is further improved by rational choice of chelants with greater affinity for Mg and tuning the optimal pH for metal complexation, thereby leading to a better yield of nanosheets. These boron-based nanosheets have been explored for their candidacy as a new class of inorganic fillers in a polymeric matrix – polyvinyl alcohol (PVA). The mechanical and thermal properties of these boron-based nanosheet-PVA nanocomposite films have been studied.